Literature Review on Non Pharmacological Method of Prevention & Management of Osteoporosis in Cerebral Palsy Children: The Impact of Weight Bearing Exercise and Mobility Training on Osteoporosis Prevention in Cerebral Palsy Children (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cerebral palsy is a non-progressive disorder of posture and movement due to insult to the developing brain. Its prevalence on the basis of population according to the reports is 1.2- 3.6 per live births. Cerebral palsy is one of the most prevalent condition which has been associated with osteoporosis due to decreased mobility. In terms of Cerebral palsy evaluation, prevention and management of osteoporosis is most important aspect. The purpose of this study is to justify that increased weight bearing activities in cerebral palsy children shows considerable improvement in BMD and the muscle strength and also improved their mobility status.Intervention A randomized literature review was conducted to find out the most suitable conventional method in prevention of Osteoporosis in Cerebral palsy children other than pharmacological intervention.Results Studies have revealed that weight bearing exercises and mobility training in cerebral palsy children has shown considerable improvement in prevention of osteoporosis and increase in BMD.Conclusion The present literature review reveals that weight bearing exercise with mobility training prevents osteoporosis which was one of the causative factor for secondary fracture in Cerebral palsy children.